Mathematics for Economics and Business - Jacques, Ian (Pearson Education Ltd, 1999)
Mathematics for Economics and Business provides a thorough foundation in mathematical methods for economics, business studies and accountancy students, whatever their mathematical background. Assuming the previous knowledge, this text is suitable for those who have not studied maths in detail before and, as the material is wide-ranging, it is also appropriate for higher level course...
Keywords: Economics; Mathematics; Non-Fiction